Implementation outcomes of reusable learning objects in health care education across three Malaysian universities: evaluation using the RE-AIM framework - Lim, Hooi Min; Teo, Chin Hai; Lee, Yew Kong; Lee, Ping Yein; Krishnan, Kuhan; Abu Hassan, Zahiruddin Fitri; Yong, Phelim Voon Chen; Yap, Wei Hsum; Sellappans, Renukha; Ayub, Enna; Hassan, Nurhanim; Shariff Ghazali, Sazlina; et al. (JMIR Publications, 2025)
Background: Current e-learning evaluation focuses on learners’ knowledge gain, satisfaction, perceptions, and attitudes; few assess the implementation outcomes of e-learning resources in teaching and learning. Objective: In this study, we used the RE-AIM (Reach, Effectiveness, Adoption, Implementation, and Maintenance) framework to systematically evaluate the implementation outcomes of reusable learning objects (RLOs) in the context of health care education. Methods: This study is a part of the Advancing Co-creation of RLOs to Digitise Healthcare Curriculum (ACoRD) project, wherein we developed and implemented 23 RLOs across 3 Malaysian universities for medical, pharmacy, and biomedical curricula. Implementation and dissemination strategies were employed. Data were collected using a self-administered web-based questionnaire and Google Analytics. Results: This study reports a cumulative RLO access of 7622 users from 48 countries (reach). Users rated RLOs as very helpful (1452/2071, 70.1%) or helpful (601/2071, 29.1%). Preassessments and postassessments showed a significant improvement in the knowledge score (21 RLOs, P<.05) and confidence level (17 RLOs, P<.05) (effectiveness). All 3 Malaysian universities adopted RLOs in the fields of professional development, primary care medicine, medicine, pediatrics, nursing, pharmacy, and biomedicine (adoption). The percentage of users who completed RLOs ranged from 5.6% (10/179) to 85% (78/92), with nonbounced users (users who viewed more than one page) ranging from 16.3% (165/1014) to 88.5% (370/418) (implementation). In the 4 months following the completion of the ACoRD project, a total of 2107 users accessed RLOs (maintenance). Conclusions: We systematically evaluated the implementation of e-learning resources by using the RE-AIM framework, informing future strategies to integrate e-learning innovations in real-world teaching and learning practices.